From flows to violence - Kalb, Don (Anthropological Theory, 2005)
Recent globalization theory reflected a chain of world historical events since the end of the Cold War. Globalization theories were tools for the making of political alliances between market liberals and political, liberals. From the mid-1990s a broad range of institutionalist social science programs showed that globalization outcomes were often better explained by institutional logics (including cultural ones) than by global flows per se. This is, among others, illustrated by the debate on global inequality data. The emerging debate on empire and imperalism is discussed as a logical offshoot of the globalization discussion just as the phenomenon itself is seen as a likely outcome of an epoch of market-driven globalization. Globalization was predicated on the emergence of a US-led transnational western state structure on behalf of the transnational capitalist class based in finance and the large corporations. Territory and space have become more important rather than less, but the explanation of regional trajectories must now be located more firmly in the interaction between local and global structures. This leads to a new agenda in the social sciences: one oriented toward common interdisciplinary programs with a limited range of core questions - about state formations, class formations, mobilizations, claim making, and associated cultural processes. Programs should be more theory driven, comparative, and in search of explanations of divergent spatial and temporal outcomes of universal process.
Keywords: alliances (international relations); civilization; cultural policy; dual polarization; empire; globalisation; globalization; imperialism; international relations; social sciences & state; transnational capitalist class